Influence of Judo Experience on Neuroelectric Activity During a Selective Attention Task - Faro, Heloiana Karoliny Campos; Machado, Daniel Gomes da Silva; Bortolotti, Henrique; do Nascimento, Paulo Henrique Duarte; Moioli, Renan Cipriano; Elsangedy, Hassan Mohamed; Fontes, Eduardo Bodnariuc (Frontiers in Psychology, 2020)
Objective: We compared the cognitive performance and neuroelectric responses during a selective attentional task in judo athletes with different levels of expertise. Methods: Judo black and white belt athletes performed both general and specific fitness tests while simultaneously completing a Stroop color-word test recorded by 64 electroencephalogram channels. Results: Cognitive behavioral performance and event-related spectral perturbation present no differences between groups. However, the topographic analysis found different neural source patterns in each group. Judo black belts compared to judo white belts presented a greater peak amplitude of P300 in the middle frontal gyrus and of N200 in the cuneus, but slower latency of P300 in the precuneus. Conclusion: Despite no difference in cognitive behavioral performance, judo expertise causes a difference in the allocation of attentional and conflict detection neural resources.